Language proficiency and immigrants' economic integration - Angela Daley; Min Hu; Casey Warman (IZA World of Labor, 2019)
Over recent decades, Western countries have admitted many immigrants from non-traditional regions (e.g. Philippines, India, China), which has coincided with poor economic integration. Language proficiency is an important determinant of economic integration; in addition to being a component of human capital, it plays a key role in facilitating the transmission of other components of human capital. Examining the strengths and weaknesses of objective and subjective measures of language proficiency is crucial for good integration policy, as is understanding the relationship between these measures and earnings, a key indicator of economic integration.
Keywords: J15; 330; immigrants; cognitive ability; language; literacy; objective measures; subjective measures; earnings